A Semantic Study Of The Arabic Word Fitnah In The Quran/ دراسة دلالية العربية لكلمة الفتنة في القرآن - Ikhsan, Arief Maulana; Yusuf, Multazam; Ifawati, Nur Ila; Firdaus, Franky Leo (Ijaz Arabi Journal of Arabic Learning, 2024)
This study aims to determine the meaning of " Al-Fitnah " in the Qur'an based on a review of semantics and Arabic. The type of research used is library research with a descriptive approach. The scope of this research is in the form of 1) semantic concepts in the Qur'an. 2) the mention of the word "Al-Fitnah" in the Qur'an. 3) the meanings contained in the word "Al-Fitnah" in every mention in the Qur'an. Data collection is carried out by library analysis in the form of books, scientific research results, news, and others. The data results are then analyzed to be reduced and presented in words based on the findings in the library. From research, it was obtained that the majority of the thirty words "Al-Fitnah" contained in the Qur'an have different meanings. This is based on the context of the verse in which the word is mentioned, the form of the word, and the Asbab Al-Nuzul of the verses in which the word is mentioned. All this can be evidenced by the emergence of different interpretations of the word "Al-Fitnah" in the Qur'an and the widespread study of the words of the Qur'an in each era.